Nitrogen fixation and N contribution by promiscuous nodulating soybeans in the southern Guinea savanna of Nigeria - Sanginga, N.; Dashiell, Kenton E.; Okogun, J.A.; Thottappilly, G. (1997)
Attention is being paid to improving the N2 fixation of promiscuous nodulating soybeans in an attempt to develop sustainable cropping systems in the moist savanna. There is however a dearth of reliable estimates of N2 fixation by these promiscuous soybeans and hardly any quantitative information is available on their residual N benefits to subsequent cereal crops grown in the southern Guinea savanna zone. The 15N isotope dilution method was used to assess symbiotic N2 fixation and response to inoculation and N contribution of three IITA promiscuous and two Brazilian soybean lines grown in the field at Mokwa (southern Guinea savanna) for two years. Rhizobial inoculation increased total N and grain yield of early maturing cultivars IAC 100 and TGX 1456–2E but did not affect the late maturing cultivar TGX 1660–19F. Both fixed N (Ndfa) and N derived from the soil were the major sources of N accounting for 84 and 75 kg N ha1 or 46 and 43%, respectively, of the plant total N. A line effect was, however, apparent with the late maturing line TGX 1660–19F deriving on the average 126 kg N ha1 or 52% of plant total N from N2 fixation compared to the early maturing line IAC 100 with 37 kg N ha1 or 38%. Total N accumulated and amounts of N2 fixed were low during early growth (V2/V3 and R1/R2 stages), but increased rapidly after this period to reach the maximum at R3/R4 and then dropped after R3/R4. The proportion of Ndfa, however, increased with the growing period. At the physiological maturity (R8), N2 fixed accounted for an average of 70% of total N accumulated in the seeds. Roots accumulated about 13% while leaves and stems had 53 and 32% of the entire plant N at R3/R4, respectively. It was estimated after grain removal, that soybean growth led to a net contribution of an average of 18 kg N ha1 to soil N. However, the N contribution ranged from - 8 to 43 kg N ha1 depending on the soybean cultivars and inoculation treat